Investigating the benefits and economic losses of the beneficiaries of Hamon International Wetland during the time of high water and drought in Sistan region - Mohaddeseh Mir; Hamid Mohammadi (علوم محیطی)
Introduction: In arid and semi-arid regions, the existence of wetlands is very important. The results obtained from various researches have shown that wetlands, in addition to environmental benefits, such as soil stabilization, temperature regulation, reducing air dryness, etc., also have economic benefits for local communities. As their livelihood depends on the wetlands, many local communities have been forced to migrate due to successive droughts and the drying up of the wetlands. Hamon Wetland is one of the natural ecosystems that has had valuable environmental and economic benefits for local communities in the Sistan region, but due to the droughts, many human and financial losses have been caused in the Sistan region. The purpose of this study is to investigate the benefits of the users of the Hamon Wetland when the wetland is flooded and to investigate the damages caused to the users during the drought.Material and methods: In this article, in order to investigate the interests of Hamon wetland users, with the consultation of local communities and previous researches, three occupations of agriculture, fishing and animal husbandry were selected for the purpose of interview. The data used in the questionnaires were extracted and the interests of farmers, fishermen and ranchers were checked by the market price method, the conditional valuation method was used to check the damage caused in the wetland.Results and discussion: The results showed that in the year 2020, the profit from the fishing sector was 7967002800 Rials. The benefits of the livestock and agriculture sectors were 77452923610 and 318165282120 Rials, respectively. The damage caused in 2022 was determined 11,683,454,1600 Rials. Also, the willingness to pay for the preservation and restoration of the Hamon Wetland was 23,445,559,200 Rials. Our findings showed that it is necessary to take serious measures in order to properly manage the wetland (Hamoun Wetland water rights) and creating alternative livelihoods for wetland beneficiaries should be on the agenda.Conclusion: This research showed that the local communities had lots of benefits with the exploitation of the lagoon but the drought caused a lot of damage to them. Therefore, according to the exploitations that took place during the flood of the lagoon, including the use of water for agriculture, the movement of fishermen to catch fish and the harvesting of fodder by ranchers and even the entry of livestock to graze in the reeds can be one of the important factors in the destruction and reduction of water resources of Hamon Wetland.